Lethal activity of beauvericin, a Beauveria bassiana mycotoxin, against the two‐spotted spider mites, Tetranychus urticae Koch. (22nd August 2019) - Al Khoury, Charbel; Guillot, Jacques; Nemer, Nabil
Abstract: The entomopathogenic fungi Beauveria bassiana (Balsamo) Vuillemin is known to produce a broad range of secondary metabolites. Beauvericin, a cyclic hexadepsipeptide, is the best known mycotoxin produced by B. bassiana ; however, reports discussing the insecticidal activity of beauvericin per se are limited. In this study, we assessed the lethal activity of beauvericin against Tetranychus urticae Koch (Acarina: Tetranychidae). In addition, screening for suitable application of the mycotoxin against T. urticae on greenhouse strawberries is discussed. Beauvericin was able to control successfully T. urticae where concentrations of 10, 100 and 1, 000 µg/g recorded mortalities of 84%, 100% and 100%, respectively, against motile stages. Furthermore, beauvericin inhibited egg hatching up to 83.3%, 69.3% and 53.3%, respectively, using the same concentrations under laboratory conditions. Under greenhouse conditions, the efficacy recorded was 52.6%, 85.7%, 72.4% and 72.4% at 1, 3, 7 and 10 days post‐inoculation, respectively. Beauvericin was efficacious under greenhouse conditions since the application increased strawberry yields while showing no phytotoxicity and ecotoxicological risk. Resistance to beauvericin was not detected initially at the unselected strain of T. urticae . Yet, the laboratory selection of populations of T. urticae exposed to beauvericin resulted in relatively resistant T. urticae strain that displayed no cross‐resistance to cyflumetofen and bifenazate. The acaricidal activity of beauvericin documented in this study would increase the efficacy of integrated pest management strategies.